(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article analyzes the theoretical and practical foundations of teaching methods for professional subjects within the modern system of technical education. It highlights the importance of methodological innovations in teaching technical disciplines, their role in the educational process, and their contribution to the development of students’ engineering thinking and professional competencies. The research is based on methodological frameworks developed by Yu.K. Babansky, E.Ya. Golant, I.T. Ogorodnikov, and other scholars, focusing on the main directions of instruction. In particular, the study substantiates the integration of verbal, visual, and practical methods in technical education, as well as the effective application of motivation and assessment techniques. The article emphasizes that the methodological activity of teachers in technical education aims to develop students’ technological thinking, foster independent inquiry, involve them in project-based learning, and enable them to solve real technical problems all of which enhance their professional training. Consequently, the methodology of teaching professional subjects in technical education is interpreted as an innovative, practice-oriented system that effectively integrates theory and practice in the learning process.